2010
DOI: 10.5056/jnm.2010.16.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Irritable Bowel Syndrome in Healthy Screenee Undergoing Colonoscopy and Laboratory Tests

Abstract: IntroductionThe prevalence of irritable bowel syndrome (IBS) after excluding organic disease has not been reported in Korea.MethodsOf 5,605 participants in a health screening program, inclusion criteria were persons who underwent colonoscopy and completed questionnaires. Exclusion criteria were persons diagnosed with colon cancer, inflammatory bowel disease, previous colectomy, and abnormal results of thyroid function tests. IBS was defined by Rome III criteria. Physical and psychological stress was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 23 publications
(41 reference statements)
5
30
0
1
Order By: Relevance
“…29, 41, 48, 52, 71 A meta-analysis of the association between smoking and low back pain from 27 cross-sectional and 13 cohort studies showed that, compared to non-smokers, smokers had greater risk of pain. There was a dose-response relation in which greater exposure to tobacco was associated with greater risk of pain.…”
Section: Introductionmentioning
confidence: 99%
“…29, 41, 48, 52, 71 A meta-analysis of the association between smoking and low back pain from 27 cross-sectional and 13 cohort studies showed that, compared to non-smokers, smokers had greater risk of pain. There was a dose-response relation in which greater exposure to tobacco was associated with greater risk of pain.…”
Section: Introductionmentioning
confidence: 99%
“…It is remarkably common, affecting 3-20% of the US population 1,2 and 2.3-9.6% of the Korean population. [3][4][5] Despite its impact on public health, IBS has received relatively little attention compared to other life-threatening diseases. 6 Healthcare decision makers, who establish payment policies and coverage, are increasingly seeking information about real-world outcomes as a basis for their decisions.…”
Section: Introductionmentioning
confidence: 99%
“…This might affect the quality of data acquired. However, a study from Nam et al14 using validated Rome III criteria in Korea gave a prevalence rate of 8.2% which is still lower than the prevalence rates observed from communities in Europe or America.…”
mentioning
confidence: 78%